Obesity-related endocrine disorders - Aleksandra Kiełczewska; Anna Kiełczewska; Grzegorz Szcześniak (Journal of Education, Health and Sport)
Introduction and Purpose: Several endocrine disorders, including diabetes, insulinoma, Cushing syndrome, hypothyroidism, polycystic ovarian syndrome, and growth hormone deficiency, are associated with obesity. The mechanisms underlying the development of obesity vary according to the abnormalities of endocrine function. This review examines the hormonal disturbances linked to obesity, extending beyond just diabetes. It explores the prevalence, clinical features, screening, diagnosis, and management of these related conditions.